Reports of National Consultations of Civil Society in Preparation for the Forward Together Conference (CARICOM Secretariat GeorgetownGY, 2002)
Presents the outcome of deliberations of civil society in 10 CARICOM countries which is a valuable input to the conference.
Contents: Barbados. - Belize. - Grenada. - Haiti. - Jamaica. - St. Kitts and Nevis. - Saint Lucia. - St. Vincent and the Grenadines. - Suriname. - Trinidad and Tobago